Genitourinary tract infection in diabetic women: Bacteriological study - Al-Bayaa, Yasmeen J. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The influence of glucose metabolism is seen in many infectious diseases, making diabetic patients more vulnerable to sepsis and other serious sequelae of bacterial invasion such as UTI and vaginitis. Patients and method: sixty two patients (women) were suffering from GUTIs consulting Al-Elwya hospital from November- 2009 to March -2010. Two samples were taken from those patients (urine samples and vaginal swabs); these samples were cultured on Blood, Chocolate, and MacConkey’s agar for isolation of bacteria. Results: The study group consists of sixty two women suffering from (GUTI), their ages range from 18-55 years. Thirty eight of them were diabetic women and twenty four of them were non- diabetic women. Twenty two of diabetic women were pregnant and sixteen of them were non- pregnant. Fifteen of non-diabetic women were pregnant and nine of them were non- pregnant. Conclusion: Diabetes and pregnancy is a significant predisposing factor for GUTIs in women.